DoHyPE: Presentation engine architecture for hypermedia debugging - Mendes, Marcos Paulo; Moreno, Marcelo Ferreira (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Hypermedia content consumption has grown due to recent technological evolution, such as communication protocols and techniques. Developing hypermedia applications has become increasingly challenging because authoring tools have limited resources for the debugging task. Thus, this work aims to propose an architecture for the presentation engine focused on the development and debugging of these applications. The architeture is agnostic regarding the hypermedia model used by the content author. For this, the architecture is based on events, allowing the communication between its components to be monitored or even synthesized. In this paper we present how the architeture can be instantiated over the Qt framework. In addition, a specialization of the propose architecture is presented taking the NCL language as a the underlying model.